Τhe fish fauna in lentic ecosystems of Greece (2022)
VARDAKAS, L., KOUTSIKOS, N., PERDIKARIS, C., PETRIKI, O., BOBORI, D., ZOGARIS, S., GIAKOUMI, S., FITOKA, E., TOMPOULIDOU, M., TSIAOUSSI, V., KOMMATAS, D., KONSTANTINIDIS, E., & ECONOMOU, A. N. (2021). Τhe fish fauna in lentic ecosystems of Greece. Mediterranean Marine Science, 23(1), 223–265. https://doi.org/10.12681/mms.28526